Unraveling the mechanism of CH3CH2OH dehydrogenation on m-ZrO2(111) surface, Au13 cluster, and Au13 cluster/m-ZrO2(111) surface: a DFT and microkinetic modeling study - Morais, Leonardo Henrique de (2024)
In this study, we investigate the dehydrogenation of ethanol and the production of CH3CHO and H2 on the m-ZrO2(111) surface, an Au13 cluster, and Au13/m-ZrO2(111) surface, using density functional theory simulations. Our primary objective is to elucidate the reaction mechanisms through thermodynamic and kinetic analysis of these catalytic processes, identifying the transition states. To further validate these findings, we employ a microkinetic model to calculate the rate constants, offering a detailed and comprehensive understanding of the reaction pathways involved. First-principles calculations were conducted using the Quantum ESPRESSO package, applying the BEEF-vdW functional for exchange and correlation interactions. The model systems were constructed in a two-dimensional supercell with periodic boundary conditions in the x and y directions, while a vacuum layer of 15 Å was introduced along the z direction to avoid interactions between periodic supercell slabs. The ethanol dehydrogenation process on both the m-ZrO2(111) surface and the Au13 cluster proceeds via two fundamental steps: the initial cleavage of the O–H bond in ethanol, yielding a CH3CH2O intermediate, followed by the formation of H2. The O–H bond dissociation occurs through interactions with lattice oxygen on the m-ZrO2(111) surface or low-coordination Au atoms in the Au13 cluster. While microkinetic modeling reveals relatively low rate constants for this pathway, the Au13/m-ZrO2(111) composite introduces an additional step in which a hydrogen atom migrates from the m-ZrO2(111) surface to the Au13 cluster. Despite this added step, our analysis shows that the activation energies for all three transition states are comparable, with the Au13/m-ZrO2(111) system demonstrating lower energy barriers and more favorable rate constants for ethanol dehydrogenation. These findings highlight the potential of Au13 clusters supported on m-ZrO2(111) for efficient and selective production of CH3CHO and H2, offering key insights for the design of advanced catalytic systems.